Phytocystatin CsinCPI-2 prevents bone loss in ligature-induced periodontitis by inhibition of inflammation and osteoclastogenesis - Da Ponte Leguizamón, Natalia [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Periodontal disease (PD) is a polymicrobial chronic inflammatory condition of the supporting tissues around the teeth, leading to the destruction of surrounding connective tissue. During the progression of PD, osteoclasts play a crucial role in the resorption of alveolar bone that eventually leads to the loss of teeth if the PD is left untreated. Therefore, the development of anti-resorptive therapies targeting bone-resorbing cells will significantly benefit the treatment of PD. Here, we demonstrate the inhibitory effect of CsinCPI-2, a novel cysteine peptidase inhibitor from the orange tree, on periodontitis-induced inflammation, alveolar bone loss and osteoclast differentiation. Using the ligature-induced periodontitis model in mice, we demonstrate that treatment with CsinCPI-2 (0.8 µg/g of body weight) significantly reduced inflammatory cell infiltrate in the connective tissue and preventes the loss of alveolar bone mass (BV/TV) caused by PD, effects associated with diminished numbers of TRAP-positive multinucleated cells. Furthermore, CsinCPI-2 significantly down-regulated the numbers of inflammatory cells expressing CD3, CD45 MAC387 and IL-1β. In vitro, CsinCPI-2 inhibited RANKL-induced TRAP+ multinucleated osteoclast formation in mouse bone marrow macrophage (BMM) cultures in a concentration-dependent manner. This effect was not due to cytotoxicity, as demonstrated by the MTT assay. CsinCPI-2 inhibited RANKL-induced mRNA expression of Acp5, Calcr and Ctsk, as well as the RANKL-induced up-regulation of Nfatc1, a crucial transcription factor for osteoclast differentiation. Our findings demonstrate that CsinCPI-2 prevents bone loss induced by PD by controlling the inflammatory process and acting directly on osteoclastogenesis, suggesting an interesting potential for CsinCPI-2 in the strategy for PD treatment.

A doença periodontal (DP) é uma condição inflamatória polimicrobiana crônica dos tecidos de suporte ao redor dos dentes, que levam à destruição do tecido conjuntivo circundante. Durante a progressão da DP, os osteoclastos desempenham um papel crucial na reabsorção do osso alveolar que, eventualmente, leva à perda de dentes caso a DP não seja tratada. Portanto, o desenvolvimento de terapias antirreabsortivas direcionadas às células responsáveis pela reabsorção óssea irão beneficiar significativamente o tratamento da DP. Aqui demonstramos o efeito inibitório da CsinCPI-2, um novo inibidor da cisteína peptidase da laranjeira na inflamação induzida por periodontite, perda óssea alveolar e diferenciação de osteoclastos. Usando o modelo de periodontite induzida por ligadura em camundongos, demonstramos que o tratamento com CsinCPI-2 (0,8 µg / g de peso corporal) reduziu significativamente o infiltrado de células inflamatórias no tecido conjuntivo e preveniu a perda de massa óssea alveolar (BV / TV) causada pela DP, efeitos estes associados a números diminuídos de células multinucleadas TRAPpositivas. Além disso, a CsinCPI-2 regulou negativamente o número de células inflamatórias que expressam CD3, CD45 MAC387 e IL-1β. In vitro, a CsinCPI-2 inibiu a formação de osteoclastos multinucleados TRAP +, induzida por RANKL em culturas de macrófagos da medula óssea (BMM) de camundongo de uma maneira dependente da concentração. Este efeito não foi devido à citotoxicidade, conforme demonstrado pelo ensaio MTT. CsinCPI-2 inibiu a expressão de mRNA induzida por RANKL de Acp5, Calcr e Ctsk, bem como a regulação positiva induzida por RANKL de Nfatc1, um fator de transcrição crucial para a diferenciação de osteoclastos. Nossos achados demonstram que a CsinCPI-2 previne a perda óssea induzida pela DP por meio do controle do processo inflamatório e ação direta na osteoclastogênese, sugerindo um potencial interessante para a CsinCPI-2 na estratégia de tratamento da DP.
Fitocistatina CsinCPI-2 evita a perda óssea na periodontite induzida por ligadura pela inibição da inflamação e osteoclastogênese
Keywords: Bone; Periodontal diseases; Periodontitis; Osteoclast; Inflammation; Osso; Doença periodontal; Periodontite; Osteoclasto; Inflamação